Research in corporate and Shari'ah governance in the Muslim world : theory and practice - Azid, Toseef; Alnodel, Ali Abdullah; Qureshi, Muhammad Azeem (Emerald Publishing Limited, 2019)
Corporate governance is oriented around the values of fairness, transparency and accountability. The comprehension and measurement of these objectives is subject to the social and economic attributes of the corporate arena. Significant bodies of intellectual work have approached an assessment of corporate governance from perspectives such as differences in management practices, economic advancements, financial management, as well as regional and country constituents. But little is known about the Islamic perspective on the conceptualization, structure and practice of corporate governance. Research in Corporate and Shari'ah Governance in the Muslim World: Theory and Practice aims to address a critical disciplinary gap between Islamic theory and the practice of the corporate sector in the Muslim World. Adopting a critical approach, the book sheds light on the impact of corporate governance on the economies of the Muslim world. It presents an examination of: Corporate governance in Islamic financial institutions. The efficiency of the Islamic Jurisprudence system. The common conceptual grounds of corporate structure in the Muslim World. The composition of business leaders in the Muslim World. Using standard tools of analysis, the book presents a logically consistent synthesis of key variables with critical economic reasoning. It extends the conventional scope of corporate governance to form a basis for common understanding of how it operates in the Muslim world. The book will prove useful to those who research, study and practice in this field.
Includes index.
Keywords: Corporate governance -- Islamic countries.; Financial institutions -- Islamic countries.; Islamic law -- Islamic countries.; Business & Economics -- Corporate Governance.; Corporate governance.; elektronické knihy; electronic books